Zarządzanie procesami logistycznymi w polskich portalach lotniczych - Tłoczyński, Dariusz (Logistics management at Polish airports, 2009)
Airports beside transport function operate also in the logistics services market. This does not mean, however, performing a strict logistics activities. It means that different logistics activities take place at airports. Airports services of passengers, cargo, baggage and ground services at many airports are executed by handling agents – firms specializing in high quality airports services. Nice attendance, short time of check-in have a beneficial influence on competitiveness of air transportation with other branches of transport. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 347-353